PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP AUDIT DELAY - Rahmawati, Selvia Eka; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Audit delay can be defined as the length of time in finishing audit which is measured from the closing date of annual book to the date of the finishing of independent audit report. This research is meant to find out empirical evidence about audit delay factors on the manufacturing companies which are listed in Indonesia Stock Exchange (IDX) from 2011 to 2013. Some factors which are examined in this research are i.e.: profitability, solvability, operation complexity, audit opinion and Public Accountant Office size as the independent variables, meanwhile the dependent variable is audit delay.The samples are manufacturing companies which are listed in IDX from 2011 to 2013. The data is the secondary data and the sample collection method has been done by using purposive sampling. The multiple linear regressions analysis is used as the analysis instruments on the 5% significance level. The samples are 96 companies with three years observation periods so 288 observation objects have been selected.The result of the examination shows that the firm size, profitability and operation complexity have negative influence to the audit delay whereas the solvability, auditorsâ opinion, and Public Accountant Office size variables do not have any influence to the audit delay.Keywords: Audit delay, Profitability, Solvability, Operation Complexity, Auditorsâ Opinion, and Size of Public Accountant Office (KAP).